Analysis of Needs and Basic Assessment of Fifth Grade Students’ Narrative Writing Skills as a Basis for Instructional Media Development - Salta Virgaria Putri; Gusti Yarmi; Linda Zakiah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
This study aims to describe the profile of fifth-grade elementary students’ narrative writing skills, analyze their learning needs in narrative writing, and formulate the characteristics of instructional media responsive to students’ actual conditions. A mixed-methods approach with a sequential exploratory design was employed, involving 31 fifth-grade students from SDN Kayu Putih 08 Pagi as participants. Quantitative data were obtained through an assessment of narrative writing skills using a four-dimensional rubric (ideas, organization, diction, spelling and punctuation) and analyzed descriptively. Qualitative data were collected through a needs analysis questionnaire and analyzed thematically. The results indicate that 70.97% of students are in the low category, with an average score of 47.98 out of 100. The main difficulty encountered is generating writing ideas (83.87%), with story writing identified as the most challenging material (64.52%). Students prefer interactive learning activities such as role-playing (35.48%) and the use of digital media (45.16%). The characteristics of responsive instructional media include being interactive and digital-based, providing systematic support at every writing stage, fostering imagination through visual stimuli, offering diverse narrative content, delivering constructive feedback, user-friendly interfaces, support for differentiated learning, and facilitating collaboration. The findings underscore the urgency of developing innovative digital media to adaptively and contextually enhance elementary students’ narrative writing skills.